Etyka i dentologia zawodów adwokata i radcy prawnego w Polsce i zawodu adwokata w Niemczech - Lewandowicz, Maria; Chyrek, Tomasz (Studia Prawa Publicznego, 2025)
The international movement of people, services, goods and capital has contributed to demand for cross-border cooperation among lawyers. The lack of harmonised rules for the practice of these professions at the supranational level prompts a search for differences and similarities in the rules for different countries. Advocates and legal advisors are professions of public trust, the practice of which involves an obligation to respect certain ethical and deontological rules of the profession. The lack of universally binding rules at the EU level means that each Member State decides independently what rules guarantee this profession is practiced correctly and in the public interest. The purpose of this article is to analyse and compare the Polish and German provisions on exercising the profession of advocate/legal advisor in terms of fulfilling the obligation of professional training and continuous improvement of qualifications. The authors conclude that despite some systemic differences, the rules for practising the profession in both countries provide a guarantee of legal services being rendered in accordance with the highest standards of knowledge and ethics. A special element distinguishing the German and Polish legal profession is the existence of a category of ‘Fachanwlat’, i.e. lawyer-specialists in a particular field. In Poland, there are no separate categories of lawyer-specialists, although within the framework of non-normative practice, attorneys independently choose their areas of specialization. However, this is not done in a formalised manner, as it is in Germany. German attorneys who have successfully completed a specialized theoretical course and have a certain number of hours worked in a particular specialization can obtain the title of Fachanwalt. In Poland, the issue of specialization within the advocacy/advocacy profession has not yet been legally regulated.